2007
DOI: 10.2165/00003088-200746060-00005
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Taurolidine following Repeated Intravenous Infusions Measured by HPLC-ESI-MS/MS of the Derivatives Taurultame and Taurinamide in Glioblastoma Patients

Abstract: Taurolidine displayed a stable pattern of derivatives in plasma in vitro, whereas in whole blood, a time- and concentration-dependent conversion was apparent. In patients, the calculated average taurolidine plasma concentration, achieved with the repeated infusion regimen, was in the antineoplastic-effective concentration range. The tissue concentrations of taurolidine and taurultame are expected to be higher than the plasma concentrations, taking into account the calculated volumes of distribution. Repeated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 16 publications
3
23
0
Order By: Relevance
“…The anti-neoplastic activity of the parent compound TRD has been demonstrated in many studies on different cancer entities in vitro as well as in vivo [18, 20, 21] . Even pilot clinical studies confirmed previous results [16, 18, 22]. Therefore, the aim of this study was to analyze anti-neoplastic effects of substance 2250 in comparison to its structural analogue TRLT, the main derivative of its effective parent compound TRD.…”
Section: Discussionsupporting
confidence: 68%
“…The anti-neoplastic activity of the parent compound TRD has been demonstrated in many studies on different cancer entities in vitro as well as in vivo [18, 20, 21] . Even pilot clinical studies confirmed previous results [16, 18, 22]. Therefore, the aim of this study was to analyze anti-neoplastic effects of substance 2250 in comparison to its structural analogue TRLT, the main derivative of its effective parent compound TRD.…”
Section: Discussionsupporting
confidence: 68%
“…Taurolidine further triggered cell shrinkage, another hallmark of eryptosis [58]. The concentration required for stimulation of eryptosis was similar to those required to trigger apoptosis of tumor cells [114][115][116][117] and to those achieved in patients [118].…”
Section: Discussionmentioning
confidence: 69%
“…52 The pharmacokinetic profile of TAU permits therapeutic use, leading to mean plasma concentrations of TAU of 83 ± 18.1 μg/ml during intravenous application in humans. 53 This value compares favorably to the facts that TAU at very low concentrations leads to a dramatic reduction or even prevention of proliferation (from ca. 2 μg/ml) and inhibition or prevention of colony formation (EC 50 = 1.2 ± 0.6 μg/ml), and at higher concentrations to acute cell killing (EC 50 = 71.2 ± 19.6 μg/ml).…”
Section: Methodsmentioning
confidence: 70%